Pengaturan Penghinaan Presiden dan Wakil Presiden Dalam Undang-Undang No 1 Tahun 2023 Tentang Kitab Undang-Undang Hukum Pidana - Prayoga, Dimas; Arfa, Nys; usman, Usman (PAMPAS: Journal of Criminal Law, 2024)
This article aims to find out and analyze the legal provisions for the criminal act of insulting the President and Vice President and to find out and analyze the urgency for the government to re-establish the article on insulting the President and Vice President. This article discusses the legal provisions governing the criminal act of insulting the President and Vice President and whether it is urgent for the government to re-establish this article. The type of research used is normative juridical. The results of the research show that the legal provisions for the insult article are contained in Article 310-321 of the Criminal Code, Article 27 Paragraph (3) of the ITE Law, Article 134, Article 136 bis, and Article 137 of the Criminal Code. Currently it is regulated in Law Number 1 of 2023 concerning the Criminal Code which consists of Article 218 Paragraphs (1) and (2), Article 219 and Article 220 Paragraphs (1) and (2). The government's urgency regarding the insult article is that the president is a symbol of the state, insult is a disgraceful act, it is felt odd if insulting the president is not regulated. Therefore the suggestion put forward is to remove the article on insulting the President and Vice President in accordance with the decision of the Constitutional Court, because the decision of the Constitutional Court is final and binding ABSTRAK Artikel ini bertujuan untuk mengetahui dan menganalisis ketentuan hukum tindak pidana penghinaan terhadap Presiden dan Wakil Presiden serta untuk mengetahui dan menganalisis urgensi pemerintah menetapkan kembali pasal penghinaan terhadap Presiden dan Wakil Presiden. Dalam tulisan ini membahas 1). Bagaimana ketentuan hukum yang mengatur tentang tindak pidana penghinaan terhadap Presiden dan Wakil Presiden? serta 2). Apakah urgensi pemerintah menetapkan kembali pasal tersebut?. Tipe penelitian yang digunakan yaitu yuridis normatif. Hasil penelitian diketahui bahwa: 1). Ketentuan hukum pasal penghinaan terdapat pada Pasal 310-321 KUHP,Pasal 27 Ayat (3) UU ITE, Pasal 134, Pasal 136 bis, dan Pasal 137 KUHP. Saat ini diatur dalam UU Nomor 1 Tahun 2023 tentang KUHP yang terdiri dari Pasal 218 Ayat (1), dan (2), Pasal 219, dan Pasal 220 Ayat (1) dan 2). Urgensi pemerintah tentang pasal penghinaan yaitu presiden merupakan simbol negara, penghinaan merupakan perbuatan tercela, dirasakan janggal kalau penghinaan presiden tidak diatur. Maka dari itu saran yang diajukan yaitu untuk menghapus pasal penghinaan Presiden dan Wakil Presiden sesuai dengan putusan Mahkamah Konstitusi, dikarenakan putusan Mahkamah Konsitusi bersifat final dan mengikat.